Learning Strategy Resulting In Interlanguage Errors UsedBy Senior High School Students Learning English As AForeign Language In MAN 1 Surakarta - Darussalam, Hanif Maghfur (2012)
The present study aims at describing the types of learning strategy which result in interlanguage errors used by high school students of MAN 1 Surakarta in writing English composition. It describes the frequency of errors, and explaining the dominant learning strategy used by the students. The type of the research is descriptive qualitative research. The writer uses elicitation technique and documentation in collecting data. The data of the present study consist of erroneous sentences taken from composition written by students of Islamic Senior High School 1 Surakarta. In collecting the data, there are at least three major stages have been done: the writer assigned the students to write English composition, the writer read every composition accurately to identify the erroneous sentences, the writers wrote down all the erroneous sentences into a list and used them as the data. In conducting this study there are at least four major tages have been done: recognition of errors, classification, description, and explanation. To recognize the errors, the writer has utilized the framework provided by Shridar. The writer has accumulated approximately 315 sentences containing different type of errors and used as the data of this study. The errors accumulated, then, classified in terms of linguistic and analyzed into types of the learning strategy. In order to find out the total number of errors as well as the frequency of the occurrence of each type of errors, all types of errors are then calculated. The highest percentage of errors recorded is learning strategy of over generalization (45.53%), the second is learning strategy of first language transfer (41.01%) and the lowest percentage of errors is categorized as learning strategy of oversimplification (15.46%). The final stage is the explanation of errors. Here the writer has attempted to explain how and why such errors exist. The sources or causes of errors are explainable through the process or the learning strategies that the students use when learning the second language. The writer reaches the conclusion from this study that the dominant learning strategy used by the students resulting in inter language errors is learning strategy of over generalization. This implies that the students have been most confronted with the interference of the target language while there are some errors due to native interference too difficult to overcome. From this, the writer can also conclude that interlanguage errors are inevitable process in foreign language learning thus teacher can use interlanguage errors wisely and positively as to investigate their learning and to help them eliminate the errors in order to develop their interlanguage system.